2014
DOI: 10.11138/mltj/2014.4.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor delivery vehicles for tendon injuries: Mesenchymal stem cells and Platelet Rich Plasma

Abstract: SummaryBackground: tendon tissue shows limited regeneration potential with formation of scar tissue and inferior mechanical properties. The capacity of several growth factors to improve the healing response and decrease scar formation is described in different preclinical studies. Besides the application of isolated growth factors, current research focuses on two further strategies to improve the healing response in tendon injuries: platelet rich plasma (PRP) and mesenchymal stem cells (MSCs). Objective: the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 101 publications
0
27
0
Order By: Relevance
“…Even with improvements in surgical interventions and rehabilitation protocols, many patients continue to have impaired mobility, and up to a third of athletes are unable to return to play after tendon rupture (13,33,34). Regenerative strategies for the management of chronic tendon injuries have mostly focused on the delivery of stem cells and growth factors to sites of injured tendon tissue to begin the healing process (4,8). As such, successful tendon repair requires a fundamental understanding of the inflammatory cascade within musculoskeletal tissue in response to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Even with improvements in surgical interventions and rehabilitation protocols, many patients continue to have impaired mobility, and up to a third of athletes are unable to return to play after tendon rupture (13,33,34). Regenerative strategies for the management of chronic tendon injuries have mostly focused on the delivery of stem cells and growth factors to sites of injured tendon tissue to begin the healing process (4,8). As such, successful tendon repair requires a fundamental understanding of the inflammatory cascade within musculoskeletal tissue in response to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies also showed that PRP induces tenogenic differentiation of adult stem cells in vitro [ 29 31 ] and PRP combined with adult stem cells promote tendon repair in vivo [ 32 , 33 ]. PRP can promote tenogenic differentiation and increase expression of such tenocyte-related genes as collagen type I, collagen type III, tenomodulin [ 29 31 ], in agreement with our results. As shown in the study, PRP promoted collagen III and tenomodulin gene expression by BMSCs and BMSC sheets in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Tenocyte gradually migrate to the wound, and type III collagen synthesis is initiated 14 . PRP has been used as source of platelet derived growth factor and transforming growth factor, and it has been reported that PRP has a positive effect on cell proliferation and collagen production, and that it induces the production of matrix-degrading enzymes and endogenous growth factors by tenocytes 11,12 . Therefore, PRP can be a remarkable environment that accelerates overall healing time in tendon repair.…”
Section: Discussionmentioning
confidence: 99%
“…PRP is a volume fraction of the plasma, having a platelet concentration above whole blood. PRP contains a set of platelet derived growth factors, including platelet derived growth factor (PDGF)-BB, transforming growth factor (TGF)-β1, insulin-like growth factor (IGF), vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), and fibroblast growth factor (FGF) 11,12 . In addition, the fibrin matrix that is generated on activation may potentially aid in tissue repair by providing a scaffold for tissue ingrowth.…”
Section: Introductionmentioning
confidence: 99%